Immature Oocyte for Fertility Preservation - Son, Weon-Young; Henderson, Sara; Cohen, Yoni; Dahan, Michael; Buckett, William (Frontiers in Endocrinology, 2019)
In vitro maturation (IVM) of human immature oocytes has been offered to women who are at risk of developing ovarian hyperstimulation syndrome (OHSS) caused by gonadotropin stimulation, such as PCO(S) patients or who have poor ovarian reserve. Cryopreservation of oocytes matured in vivo obtained in IVF cycles has improved after implementing the vitrification method and many successful results have been reported. Now, this procedure can be successfully offered to fertility preservation programs for patients who are in danger of losing their ovarian function due to medical or social reasons, and to oocyte donation programs. This vitrification technique has also been applied to cryopreserve oocytes obtained from IVM program. Some advantages of oocytes vitrification related with IVM are: (1) eliminating costly drugs and frequent monitoring; (2) completing treatment within 2 to 10 days (3) avoiding the use of hormones in cancer patients with hormone-sensitive tumors; and (4) retrieving oocytes at any point in menstrual cycle, even in the luteal phase. In addition, immature oocytes can also be collected from extracorporeal ovarian biopsy specimens or ovaries during caesarian section. Theoretically, there are two possible approaches for preserving immature oocytes: oocyte cryopreservation at the mature stage (after IVM) and oocyte cryopreservation at the Germinal Vesicle (GV)-stage (before IVM). Both vitrification of immature oocyte before/after IVM is not currently satisfactory. Nevertheless, many IVF centers worldwide are doing IVM oocyte cryopreservation as one of the options to preserve fertility for female cancer. Therefore, more studies are urgently required to improve IVM- and vitrification method to successfully preserve oocytes collected from cancer patients. In this review, present oocyte maturation mechanisms and recent progress of human IVM cycles will be discussed first, followed by some studies of the vitrification of human IVM oocyte.